Цифрова нерівність як стратифікаційний модус інформаційного суспільства - Гудзенко, Олеся Зиновіївна; Gudzenko, Olesya; Щепова, Діана Романівна; Shchepova, Diana (Дніпровський національний університет імені Олеся Гончара, 2022)
Соціокультурні зміни, пов’язані з розвитком інформаційних і цифрових технологій призводять до структурних зрушень у суспільстві – створюється новий формат гетерогенності елементів структури і системи соціальних відносин між цими елементами. Як наслідок в умовах сучасного інформаційного суспільства виникають нові класоутворюючі стратифікаційні критерії нерівності, які стосуються наявності/відсутності цифрових ресурсів та можливостей доступу до них. Важливим в цьому сенсі буде наявний рівень цифрового капіталу агента соціальної системи. Вплив цифровізації і ІКТ-технологій призводить до того, що «в інформаційному суспільстві класи змінюються соціально недиференційованими «інформаційними спільнотами» (Й.Масуда). При підготовці наукової роботи були використані загальнонаукові методи пізнання – аналізу та синтезу, компаративістики, узагальнення та безпосередньо соціологічний метод – вторинний аналіз даних. Дана наукова робота присвячена дослідженню впливу діджиталізації на процеси структурування українського суспільства і соціологічній концептуалізації нового модусу стратифікаційної системи – цифрової нерівності. В статті охарактеризовані основні риси інформаційного суспільства, сформульовані маркери цифрової нерівності, запропоновано концептуалізацію понять цифрова бідність і цифровий капітал. Стаття має теоретичне значення для подальшої розробки емпіричних маркерів фіксації цифрової нерівності при дослідженні структурних вимірів сучасного суспільства. Sociocultural changes associated with the development of information and digital technologies lead to structural shifts in society – a new format of heterogeneity of structural elements and the system of social relations between these elements is created. As a result, in the conditions of the modern information society, new class-forming stratification criteria of inequality arise, which relate to the presence/absence of digital resources and access to them. The existing level of digital capital of the agent of the social system will be important in this sense. The influence of digitization and ICT technologies leads to the fact that “in the information society, classes are replaced by socially undifferentiated “information communities” (E.Masuda). “Small” economic forms are replacing traditional bulky corporations: individual activity at home, “electronic college” (O.Toffler), changes in traditional printing with “electronic books”, changes in ideology, transformation of unemployment into secured leisure (H.Evans)”. The purpose of the article is to develop the conceptual basis for the study of digital inequality in the conditions of a digitalized society. The methodological basis of the article is the structural-constructivist paradigm, the concepts of the information and network society of E.Masud, M. Castells, and O.Tofler, theoretical aspects of the scientific works of Z.Bauman, J.C.Ramo, M.Rogers. In the preparation of the scientific work, general scientific methods of cognition - analysis and synthesis, comparative studies, generalization and directly sociological method - secondary data analysis were used. This scientific work is dedicated to the study of the impact of digitalization on the processes of structuring Ukrainian society and the sociological conceptualization of a new mode of the stratification system - digital inequality. The article characterizes the main features of the information society, formulates markers of digital inequality, offers a conceptualization of the concepts of digital poverty and digital capital. The article has theoretical significance for the further development of empirical markers of fixing digital inequality in the study of structural dimensions of modern society.
Digital inequality as a mode of stratification Information society
Keywords: діджиталізація; digitalization; цифровий розрив; digital divide; цифровий капітал; digital capital; цифрові навички; digital skills; цифрова бідність; digital poverty